Lower-Risk Myelodysplastic Syndrome (MDS) Patients Exhibit Diminished Proteasome Proteolytic Activity and High Intracellular Reactive Oxygen Species (ROS) Levels - Zafeiropoulou, Kalliopi; Kalampounias, Georgios; Alexis, Spyridon; Androutsopoulou, Theodosia; Katsoris, Panagiotis; Symeonidis, Argiris (Curēus (Palo Alto, CA), 2023)
Myelodysplastic syndromes (MDS) constitute a heterogeneous group of clonal hematopoietic stem cell disorders characterized by ineffective hematopoiesis and an elevated risk of transformation to acute myeloid leukemia (AML). Available disease-modifying treatment approaches are limited. The ineffectiveness of proteasome inhibitors (PIs) in MDS patients is currently investigated, although it is unclear whether they rapidly develop resistance to PIs or whether proteasome proteolytic activity (PPA) is constitutively lower in the hematopoietic cells of these patients, thus limiting treatment effectiveness. We investigated 20 patients with MDS, categorized according to the International Prognostic Scoring System (IPSS) into a lower- or a higher-risk group. Peripheral blood mononuclear cells, bone marrow mononuclear cells, and cluster of differentiation 34-positive (CD34+) cells were isolated and assessed for the chymotrypsin-like activity of the proteasome and β5 subunit accumulation. Additionally, intracellular reactive oxygen species (ROS) generation was screened. The lower-risk patient group (n=10) exhibited significantly lower proteasome activity (p<0.001) compared to both the higher-risk group (n=10) and healthy subjects (n=10). Furthermore, the lower-risk group had elevated oxidative stress levels (p<0.0001) and reduced β5 subunit expression (p=0.0286). Both parameters were shown to be associated with transfusion dependency, since transfusion-dependent patients (n=5 in each subgroup) had decreased proteasome activity and simultaneously exhibited higher ROS levels. Our results indicate that reduced β5 expression might potentially explain PIs' ineffectiveness in lower-risk MDS, elucidating the importance of the risk group in the selection of the proper treatment algorithm.